The Effect of Patriarchy Towards Women's Oppression of Freedom in Enola Holmes: The Case of The Missing Marquess by Nancy Springer - Sava Anindya Anugerah Putri; Siti Hafsah (Prologue: Journal on Language and Literature, 2023)
This thesis aims to analyze the effect of patriarchy towards the oppression of women’s freedom in the novel Enola Holmes: The Case of The Missing Marquess. The theory used in this research is the theory of feminism specifically liberal feminism proposed by Mary Wollstonecraft. The method used in this research is a descriptive qualitative research method. The researcher found that there are several forms of oppression of women’s freedom based on forms of patriarchy, such as public and private patriarchy. The oppression such as, the oppression of freedom in the form of Education, Voting Rights, and Individual Rights. The oppression was dominant happened in private patriarchy form. Those oppression resulted a women’s resistance from women who wanted to resist the patriarchal actions experienced by the female character in this object research.